High performance computing : modern systems and practices - Sterling, Thomas Lawrence; Anderson, Matthew; Brodowicz, Maciej; Bell, C. Gordon (Elsevier, Morgan Kaufmann, 2018)
High Performance Computing: Modern Systems and Practices is a fully comprehensive and easily accessible treatment of high performance computing, covering fundamental concepts and essential knowledge while provideing key skills training. Because an understanding of HPC is central to achieving advances in science, engineering, commerce, industry, national security, and the Internet itself, system engineers need guidance on how to properly leverage these vital resources. With this book, domain scientists learn how to use supercomputers as a key tool in their quest for new knowledge. Practicing engineers will discover how supercomputers can employ HPC systems and methods to the design and simulation of innovative products. Students can begin their careers with an understanding of possible directions for future research and development in HPC. Those who maintain and administer commodity clusters will find this textbook provides essential coverage of what HPC systems do and how they are used. Covers enabling technologies, system architectures and operating systems, parallel programming languages and algorithms, scientific visualization, correctness and performance debugging tools and methods, GPU accelerators and big data problems. Provides numerous examples exploring the basics of supercomputing while providing practical training in the real use of high end computers.Includes informative and practical examples help build knowledge and skills through incremental steps.Features sidebars of background and context to present a live history and culture of this unique field.Online resources include recorded lectures from the authors' HPC courses taught using this book.